مصطفى عبداللطيف السحرتي ناقدا - سميسم، وئام كاظم (جامعة الكوفة - كلية الآداب, 2009)
Mustafa Abdul Latif AL-Sahrti is considering as one of the most distinguished personalities of the Arabic contemporary literature. He was a pointer of the critical movement through his poetry and deep studies during thirty years. \ He wrote many studies in the political weekly magazines, weekly statement, and Appolo magazine, and etc. \ In criticism, many of his works were considered as main references for those who write contemporary poetry and literature. \ This search tries to submit a remarkable part fo Al-Sahartie's critical study. As a conclusion, the search proved that Al-Saharti has taken part in the field of the Arabic criticism theorizing and implicationally; treated many issues that were points of disagreement for many critics specially the issue of renewal. The search who criticized as a result of wide experience in criticism and intellect .
Keywords: الشعر و الأخلاق -- السحرتي ، مصطفى عبداللطيف -- النقاد العرب -- النقد الأدبي -- نقد القصة العربية -- نقد الشعر -- الأدب العربي